O istocie języka w procesie edukacji ze szczególnym uwzględnieniem procesu kształcenia językowego - Rumianowska, Agnieszka (Studia Edukacyjne, 2020)
The article names the problem of a language, its essence and the way the reality is described by it. The author undertakes an attempt to integrate pragmatic, effictive and correct aspects of language education with the problem of relavancy and the meaning of language aktivities. She pays special attention to deep intimate hermeneutic relationship beetween human being and his language and the moral and etical issues of language education and language activity. In the second part of the article the autor indicates the necessity of integrating pragmatic purposes connected with language knowlege and communicative skills with the purposes of general education, which creates the possibility of cognitive and emotional development of pupils.